2022
DOI: 10.3390/cells11132023
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonists in Neurodegeneration: Neurovascular Unit in the Spotlight

Abstract: Defects in brain energy metabolism and proteopathic stress are implicated in age-related degenerative neuronopathies, exemplified by Alzheimer’s disease (AD) and Parkinson’s disease (PD). As the currently available drug regimens largely aim to mitigate cognitive decline and/or motor symptoms, there is a dire need for mechanism-based therapies that can be used to improve neuronal function and potentially slow down the underlying disease processes. In this context, a new class of pharmacological agents that achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 286 publications
0
10
0
Order By: Relevance
“…In addition, GLP-1RA has been shown, in animal studies, to improve cognitive function, reduce cerebral accumulation of amyloid-b peptide in Alzheimer’s disease, influence dopamine levels in Parkinson’s disease and demonstrated beneficial effects on brain ischaemia. Therefore, there is the potential of these agents to maintain neuronal integrity and improve neurodegenerative diseases in humans [ 154 ]. The effect of these new therapies on skeletal muscles and muscle function needs future investigation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, GLP-1RA has been shown, in animal studies, to improve cognitive function, reduce cerebral accumulation of amyloid-b peptide in Alzheimer’s disease, influence dopamine levels in Parkinson’s disease and demonstrated beneficial effects on brain ischaemia. Therefore, there is the potential of these agents to maintain neuronal integrity and improve neurodegenerative diseases in humans [ 154 ]. The effect of these new therapies on skeletal muscles and muscle function needs future investigation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Treatment of Liraglutide in a T-cell driven adoptive transfer colitis mouse model upregulated expression of IL-33, mucin 5b, and CCL20 in murine Brunner’s glands and improved colitis ( Bang-Berthelsen et al, 2016 ). GLP-1RAs have shown promising efficacies in cellular and animal neurodegenerative models including Alzheimer’s disease and Parkinson’s disease (reviewed in Monti et al, 2022 ). Retrospective analysis of pooled clinical trials of GLP-1RAs in T2D patients for 3.6 years, including LEADER, SUSTAIN 6 and PIONEER 6, indicated that the incidence of dementia in T2D patients treated with Liraglutide or Semaglutide was 53% less than patients on placebo ( Norgaard et al, 2022 ).…”
Section: Gut-restrictive Gpr40 Agonist For Metabolic Disorders and Be...mentioning
confidence: 99%
“…The insulin level in neuronal cells is determined by the rate at which it crosses the BBB by receptor-mediated transport and diffusion mechanisms. GLP-1 (glucagon-like peptide-1) regulates blood glucose levels by reducing glucagon secretion and decreasing food intake [ 10 ]. In T2DM, the GLP-1 receptor (GLP-1R) is responsible for the genes’ regulatory elements involved in neuronal survival and function.…”
Section: Introductionmentioning
confidence: 99%
“…In T2DM, the GLP-1 receptor (GLP-1R) is responsible for the genes’ regulatory elements involved in neuronal survival and function. As GLP-1 agonists, they are used as targets in neurological disorders [ 10 ]. Some studies have shown that GLP-R is activated via the cAMP (cellular levels of cyclic AMP)/PKA (Protein Kinase A) pathways and is involved in neuroprotective action.…”
Section: Introductionmentioning
confidence: 99%